Multicomponent iron-silicon-aluminum soft magnetic component and method for its production by metal injection molding
Patent Information
- Application Number
- CN202611190002.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]由于多元铁硅铝合金材料本身脆性大、易氧化,通过金属注射成型工艺制备多元铁硅铝软磁件存在成型难、制品烧结时容易开裂,最终制备出来的软磁件制品综合性能不达标等难题
本发明所提供的多元铁硅铝软磁件的金属注射成型制备方法,通过按质量百分数计包括:Fe粉83~84%、Si粉7~7.5%、A1粉 5.5~6%、Cr粉1.0~1.2%、Ni粉2.2~2.5%、Cu粉0.3~0.4%的多元铁硅铝合金粉作为金属粉原料与聚甲醛、聚乙烯、硬脂酸以及抗氧化剂按设定比例混合在密炼机混炼造粒,将造粒得到的合金喂料颗粒依次进行注射成型、催化脱脂、热脱脂、烧结,磁场退火相关工艺制备得到高频低损耗、耐蚀性和韧性强的多元铁硅铝软磁件,实现通过金属注射成型工艺批量生产多元铁硅铝软磁件。
Smart Images

Figure CN122999984A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallurgical technology, specifically to a multi-element iron-silicon-aluminum soft magnetic component and its metal injection molding preparation method. Background Technology
[0002] Soft magnetic materials are core functional materials in the fields of power electronics and electromagnetic conversion. Multi-element iron-silicon-aluminum soft magnetic alloys, due to their near-zero magnetocrystalline anisotropy, near-zero magnetostriction, low high-frequency loss, and excellent corrosion resistance, are widely used in precision electronic devices such as high-frequency inductors and micro-sensors. Currently, the fabrication of multi-element iron-silicon-aluminum soft magnetic components mainly employs processes such as powder metallurgy and rolling. However, powder metallurgy can only produce simple bulk and sheet materials and cannot achieve near-net-shape forming of three-dimensional irregular and micro-sized soft magnetic components.
[0003] Metal injection molding has advantages such as near-net-shape forming, good batch consistency, high material utilization, and the ability to manufacture complex-shaped parts, making it the optimal manufacturing process for complex soft magnetic parts.
[0004] Due to the inherent brittleness and susceptibility to oxidation of multi-element iron-silicon-aluminum alloy materials, the preparation of multi-element iron-silicon-aluminum soft magnetic parts by metal injection molding presents challenges such as difficult molding, easy cracking during sintering, and ultimately, substandard overall performance of the soft magnetic parts.
[0005] These problems restrict the application of metal injection molding in the field of multi-element iron-silicon-aluminum soft magnetic components: it is difficult to achieve large-scale production of multi-element iron-silicon-aluminum soft magnetic components, it is impossible to guarantee high-precision dimensional control of multi-element iron-silicon-aluminum soft magnetic components, and the produced multi-element iron-silicon-aluminum soft magnetic components cannot meet the requirements of low loss in high-frequency scenarios.
[0006] Therefore, developing a preparation method that is compatible with metal injection molding process, can maintain the inherent high frequency, low loss and excellent corrosion resistance of multi-element iron-silicon-aluminum soft magnetic alloys, and at the same time has good formability, so as to realize the large-scale and high-precision production of complex-shaped soft magnetic parts, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a method for preparing multi-element iron-silicon-aluminum soft magnetic components by metal injection molding, comprising the following steps: S10, the following raw materials—multi-component iron-silicon-aluminum alloy powder, polyoxymethylene, polyethylene, stearic acid, and antioxidant—are added to a mixer in a set proportion and mixed. The mixture is then granulated using a granulator to obtain alloy feed pellets. The multi-component iron-silicon-aluminum alloy powder comprises, by mass percentage: 83-84% Fe powder, 7-7.5% Si powder, 5.5-6% Al powder, 1.0-1.2% Cr powder, 2.2-2.5% Ni powder, and 0.3-0.4% Cu powder. S20, alloy feed particles are fed into the injection molding machine, the injection temperature of the injection molding machine is controlled to melt the alloy feed particles, and the molten alloy feed particles are injected into the alloy green part. S30, the alloy green blank is subjected to catalytic degreasing to obtain a catalytically degreased alloy green blank; S40, the catalytically degreased alloy green blank is sequentially subjected to hot degreasing and sintering to obtain an alloy sintered green blank; S50 involves heating the alloy sintered blank in a reducing gas atmosphere and applying a DC magnetic field to achieve magnetic field heat treatment of the alloy sintered blank. After cooling, a multi-element iron-silicon-aluminum soft magnetic component is obtained.
[0008] Preferably, the method further includes the following steps before step S10: S01, based on 100% total mass of metal raw materials, provides the following metal raw materials: Fe 83~84%, Si 7~7.5%, Al 5.5~6%, Cr 1.0~1.2%, Ni 2.2~2.5%, Cu 0.3~0.4%; S02, after mixing the various metal raw materials Fe, Si, Al, Cr, Ni and Cu, put them into the vacuum induction melting furnace of the gas atomization equipment; evacuate the vacuum induction melting furnace, heat it to completely melt and refine the various metal raw materials to obtain a multi-element alloy liquid; S03, the multi-element alloy liquid is transferred to the intermediate package of the gas atomization equipment. After flowing out through the leak in the intermediate package, nitrogen is used as the atomization medium to atomize the multi-element alloy liquid under atomization pressure to obtain the initial multi-element iron-silicon-aluminum alloy powder. S04, the initial multi-element iron-silicon-aluminum alloy powder is sieved to remove large alloy powder particles, and the multi-element iron-silicon-aluminum alloy powder is obtained.
[0009] Preferably, the morphology of the multi-element iron-silicon-aluminum alloy powder is spherical, with a sphericity greater than or equal to 0.85; The particle size of the multi-element iron-silicon-aluminum alloy powder is 0.1-40μm.
[0010] Preferably, the antioxidant is a hindered phenolic antioxidant.
[0011] Preferably, step S10, which involves mixing the following raw materials—multi-component iron-silicon-aluminum alloy powder, polyoxymethylene, polyethylene, stearic acid, and antioxidant—in a mixer, followed by granulation using a granulator to obtain alloy feed pellets, specifically includes: S11, the multi-element iron-silicon-aluminum alloy powder is put into the internal mixer for preheating treatment; S12, polyoxymethylene, polyethylene, stearic acid and antioxidant are put into a mixer and heated and mixed with preheated multi-element iron-silicon-aluminum alloy powder to obtain a uniform mixture. S13, the mixture is fed into the granulator, which extrudes and granulates the mixture to obtain alloy feed pellets.
[0012] Preferably, step S20, which involves feeding alloy feed particles into an injection molding machine, controlling the injection temperature of the machine to melt the alloy feed particles, and injection molding the molten alloy feed particles into an alloy green part, specifically includes: S21, put the alloy feed particles into the injection molding machine, set the temperature of the heating zone of the injection molding machine, and melt the alloy feed particles; S22 controls the screw speed and back pressure of the injection molding machine, so that the molten alloy feedstock is conveyed forward in the injection molding machine and injected into the mold cavity; S23, after injection is completed, the process enters the holding pressure stage. After holding pressure is completed, the part is ejected from the mold cavity after cooling to obtain the alloy green blank.
[0013] Preferably, the step of S30, which involves catalytically degreasing the alloy green part to obtain a catalytically degreased alloy green part, specifically includes: S31, place the alloy green blank in a heated catalytic degreasing furnace and replace the air in the furnace under nitrogen protection; S32, oxalic acid is vaporized and then introduced into the furnace along with the carrier gas to catalytically degrease the alloy green blanks, resulting in catalytically degreased alloy green blanks.
[0014] Preferably, the step of S40, which involves sequentially hot degreasing and sintering the catalytically degreased alloy green part to obtain an alloy sintered green part, specifically includes: S41, the catalytic degreasing alloy green blank is placed in a vacuum furnace. After evacuation, the catalytic degreasing alloy green blank in the vacuum furnace is heated by step heating, so that the furnace temperature is raised to multiple incremental preset temperature points in sequence, and the temperature is held at each preset temperature point for a set time to obtain the hot degreasing alloy green blank. S42, continue heating the hot degreased alloy green billet in the vacuum furnace to sinter and obtain a cooked billet; S43, the sintered billet is cooled to obtain the alloy sintered billet.
[0015] Preferably, the step of heating the alloy sintered billet in a reducing gas atmosphere and applying a DC magnetic field to achieve magnetic field heat treatment of the alloy sintered billet, and obtaining a multi-element iron-silicon-aluminum soft magnetic component after cooling, specifically includes: S51, the alloy sintered billet is heated to 500~600℃ in a reducing gas atmosphere, held for 2~3h and a DC magnetic field of 0.1~0.3T is applied simultaneously, so that the direction of the DC magnetic field is consistent with the magnetization direction of the alloy sintered billet, thereby realizing the magnetic field heat treatment of the alloy sintered billet. S52, the alloy sintered billet after magnetic field heat treatment is cooled at a cooling rate of 3~5℃ / min, and after cooling to room temperature, a multi-element iron-silicon-aluminum soft magnetic part is obtained.
[0016] The present invention also provides a multi-element iron-silicon-aluminum soft magnetic component, comprising the following components by mass percentage: Fe 83~84%, Si 7~7.5%, Al 5.5~6%, Cr 1.0~1.2%, Ni 2.2~2.5%, Cu 0.3~0.4%; The multi-element iron-silicon-aluminum soft magnetic component is prepared by the metal injection molding method described above.
[0017] The beneficial effects of this invention are as follows: The metal injection molding preparation method for multi-element iron-silicon-aluminum soft magnetic parts provided by this invention involves using a multi-element iron-silicon-aluminum alloy powder, comprising by weight percentage: 83-84% Fe powder, 7-7.5% Si powder, 5.5-6% Al powder, 1.0-1.2% Cr powder, 2.2-2.5% Ni powder, and 0.3-0.4% Cu powder, as the metal powder raw material. This powder is mixed with polyoxymethylene, polyethylene, stearic acid, and antioxidants in a set ratio and granulated in a mixer. The granulated alloy feed particles are then subjected to injection molding, catalytic degreasing, thermal degreasing, sintering, and magnetic field annealing processes to prepare high-frequency, low-loss, corrosion-resistant, and tough multi-element iron-silicon-aluminum soft magnetic parts. This method enables the mass production of multi-element iron-silicon-aluminum soft magnetic parts through metal injection molding. Attached Figure Description
[0018] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a schematic diagram of the metal injection molding process for preparing the multi-element iron-silicon-aluminum soft magnetic component of the present invention.
[0019] Figure 2 yes Figure 1 A further detailed flowchart of the S10 process.
[0020] Figure 3 yes Figure 1 A further detailed flowchart of the S20 process.
[0021] Figure 4 yes Figure 1 A further detailed process diagram of the S30.
[0022] Figure 5 yes Figure 1 A further detailed flowchart of the S40 process.
[0023] Figure 6 yes Figure 1 A further detailed flowchart of the S50 process.
[0024] Figure 7 This is another schematic diagram of the metal injection molding preparation method for the multi-element iron-silicon-aluminum soft magnetic parts of the present invention. Detailed Implementation
[0025] The following drawings disclose several embodiments of the present invention. For clarity, many practical details will be described in the following description. However, it should be understood that these practical details are not intended to limit the invention. That is, in some embodiments of the invention, these practical details are not essential. Furthermore, for the sake of simplicity, some conventional structures and components will be shown in the drawings in a simple schematic manner.
[0026] It should be noted that all directional indications in the embodiments of the present invention, such as up, down, left, right, front, back, etc., are only used to explain the relative positional relationship and movement of the components in a specific posture as shown in the attached figure. If the specific posture changes, the directional indication will also change accordingly.
[0027] Furthermore, in this invention, the use of terms such as "first," "second," etc., is for descriptive purposes only and does not specifically refer to any order or sequence, nor is it intended to limit the invention. They are merely used to distinguish items or operations described using the same technical terms and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the technical solutions of the various embodiments can be combined with each other, but only if they are feasible for those skilled in the art. If a combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.
[0028] To further understand the invention's content, features, and effects, the following embodiments are provided, and detailed descriptions are given below in conjunction with the accompanying drawings: Reference Figure 1 , Figure 1 This is a schematic flowchart of the metal injection molding preparation method for the multi-element iron-silicon-aluminum soft magnetic component of the present invention. The metal injection molding preparation method for the multi-element iron-silicon-aluminum soft magnetic component provided by the present invention includes the following steps: S10: The following raw materials, namely multi-element iron-silicon-aluminum alloy powder, polyoxymethylene, polyethylene, stearic acid and antioxidant, are added into a mixer in a set ratio and mixed. The mixture is then granulated by a granulator to obtain alloy feed pellets.
[0029] The raw materials, by weight percentage, comprise: 91% multi-element iron-silicon-aluminum alloy powder, 6% polyoxymethylene, 1.5% polyethylene, 1% stearic acid, and 0.5% antioxidant. Preferably, the antioxidant is a hindered phenolic antioxidant. The polyoxymethylene, polyethylene, stearic acid, and antioxidant are combined to form the binder used in the injection molding of the product of this invention.
[0030] The multi-element iron-silicon-aluminum alloy powder comprises, by mass percentage: 83-84% Fe powder, 7-7.5% Si powder, 5.5-6% Al powder, 1.0-1.2% Cr powder, 2.2-2.5% Ni powder, and 0.3-0.4% Cu powder.
[0031] In this step, the introduction of three metallic elements, Ni, Cu, and Cr, into the multi-element iron-silicon-aluminum alloy powder can improve the compatibility of the multi-element iron-silicon-aluminum alloy with metal injection molding and prevent the blank from cracking after subsequent metal injection molding.
[0032] See Figure 2 , Figure 2 for Figure 1 A detailed flowchart of the S10 process is shown below. S10 involves mixing the following raw materials—multi-element iron-silicon-aluminum alloy powder, polyoxymethylene, polyethylene, stearic acid, and antioxidant—in a mixer, followed by granulation to obtain alloy feed pellets. The specific steps include: S11, the multi-element iron-silicon-aluminum alloy powder is put into the internal mixer for preheating treatment; S12 involves adding polyoxymethylene, polyethylene, stearic acid, and antioxidants into a mixer and heating and mixing them with preheated multi-component iron-silicon-aluminum alloy powder to obtain a uniform mixture.
[0033] S13, the mixture is fed into the granulator, which extrudes and granulates the mixture to obtain alloy feed pellets.
[0034] S20: Alloy feed particles are fed into the injection molding machine, and the injection temperature of the injection molding machine is controlled to melt the alloy feed particles. The molten alloy feed particles are then injected into the alloy blank.
[0035] See Figure 3 , Figure 3 for Figure 1 A detailed flowchart of S20 is shown below. S20, the step of feeding alloy feed particles into an injection molding machine, controlling the injection temperature to melt the alloy feed particles, and injection molding the molten alloy feed particles into an alloy green part, specifically includes: S21, the alloy feed particles are fed into the injection molding machine, and the temperature of the heating zone of the injection molding machine is set to melt the alloy feed particles.
[0036] The heating zone temperature of the injection molding machine mentioned in this step is 170℃-190℃.
[0037] S22 controls the screw speed and back pressure of the injection molding machine, so that the molten alloy feedstock is conveyed forward in the injection molding machine and injected into the mold cavity.
[0038] S23, after injection is completed, the process enters the holding pressure stage. After holding pressure is completed, the part is ejected from the mold cavity after cooling to obtain the alloy green blank.
[0039] The injection pressure is 90MPa-130MPa, the holding time is 6s-10s, and the injection speed is 30mm / s-50mm / s.
[0040] S30, the alloy green blank is subjected to catalytic degreasing to obtain a catalytically degreased alloy green blank.
[0041] See Figure 4 , Figure 4 for Figure 1 A detailed flowchart of S30 is shown below. S30, the step of catalytically degreasing the alloy green blank to obtain a catalytically degreased alloy green blank, specifically includes: S31, place the alloy green blank in a heated catalytic degreasing furnace and replace the air in the furnace under nitrogen protection.
[0042] In step S31, the heating temperature range is 90℃~120℃, and the nitrogen flow rate range is 0.3L / min~0.5L / min.
[0043] S32 vaporizes oxalic acid and introduces it into the furnace along with the carrier gas to catalytically degrease the alloy green blanks, thereby obtaining catalytically degreased alloy green blanks.
[0044] In this step, the oxalic acid injection rate ranges from 1 g / min to 3 g / min. Continuous heat preservation is required during the catalytic degreasing process of the alloy green blank, with a holding time ranging from 4 h to 6 h.
[0045] S40, the catalytically degreased alloy green blank is sequentially subjected to hot degreasing and sintering to obtain an alloy sintered green blank.
[0046] See Figure 5 , Figure 5 for Figure 1 A detailed flowchart of S40 is shown below. S40, which involves sequentially hot degreasing and sintering the catalytically degreased alloy green blank to obtain a sintered alloy blank, specifically includes the following steps: S41, the catalytic degreasing alloy green blank is placed in a vacuum furnace. After evacuation, the catalytic degreasing alloy green blank in the vacuum furnace is heated by step heating, so that the furnace temperature is raised to multiple incremental preset temperature points in sequence, and the temperature is held at each preset temperature point for a set time to obtain the hot degreasing alloy green blank.
[0047] The plurality of incremental preset temperature points include: a first preset temperature point and a second preset temperature point. The first preset temperature point has a value range of 300~450℃, and the corresponding first heat preservation time has a value range of 60~90min. The second preset temperature point has a value range of 600~650℃, and the corresponding second heat preservation time has a value range of 60~90min.
[0048] S42, continue heating the hot degreased alloy green billet in the vacuum furnace to sinter and obtain a cooked billet; The sintering temperature ranges from 1150 to 1250°C, and the sintering time is 3 to 5 hours.
[0049] S43, the sintered billet is cooled to obtain the alloy sintered billet.
[0050] Specifically, the cooling of the sintered billet in S43 includes controlling the temperature of the sintering furnace at a cooling rate of 5~10℃ / min to obtain the alloy sintered billet.
[0051] S50 involves heating the alloy sintered blank in a reducing gas atmosphere and applying a DC magnetic field to achieve magnetic field heat treatment of the alloy sintered blank. After cooling, a multi-element iron-silicon-aluminum soft magnetic component is obtained.
[0052] See Figure 6 , Figure 6 yes Figure 1 A detailed flowchart of the S50 process is shown below. S50 involves heating the alloy sintered blank in a reducing gas atmosphere and applying a DC magnetic field to achieve magnetic field heat treatment of the alloy sintered blank. After cooling, the resulting multi-element iron-silicon-aluminum soft magnetic component is obtained. The specific steps include: S51, the alloy sintered billet is heated to 500~600℃ in a reducing gas atmosphere, held for 2~3h and a DC magnetic field of 0.1~0.3T is applied simultaneously, so that the direction of the DC magnetic field is consistent with the magnetization direction of the alloy sintered billet, thereby realizing the magnetic field heat treatment of the alloy sintered billet.
[0053] S52, the alloy sintered billet after magnetic field heat treatment is cooled at a cooling rate of 3~5℃ / min, and after cooling to room temperature, a multi-element iron-silicon-aluminum soft magnetic part is obtained.
[0054] Further, see Figure 7 , Figure 7 This is another schematic flowchart of the metal injection molding method for preparing the multi-element iron-silicon-aluminum soft magnetic component of the present invention. The method further includes the following steps before step S10: S01, based on 100% of the total mass of metal raw materials, provides the following metal raw materials: Fe 83~84%, Si 7~7.5%, Al 5.5~6%, Cr 1.0~1.2%, Ni 2.2~2.5%, Cu 0.3~0.4%.
[0055] S02, the various metal raw materials Fe, Si, Al, Cr, Ni and Cu are mixed and put into the vacuum induction melting furnace of the gas atomization equipment; the vacuum induction melting furnace is evacuated and heated to completely melt and refine the various metal raw materials to obtain a multi-element alloy liquid.
[0056] S03, the multi-element alloy liquid is transferred to the intermediate package of the gas atomization equipment. After flowing out through the leak in the intermediate package, nitrogen is used as the atomization medium to atomize the multi-element alloy liquid under atomization pressure to obtain the initial multi-element iron-silicon-aluminum alloy powder.
[0057] S04, the initial multi-element iron-silicon-aluminum alloy powder is sieved to remove large alloy powder particles, and the multi-element iron-silicon-aluminum alloy powder is obtained.
[0058] The multi-element iron-silicon-aluminum alloy powder has a spherical morphology with a sphericity greater than or equal to 0.85. The particle size of the multi-element iron-silicon-aluminum alloy powder is 0.1-40 μm. Specifically, in step S04, a sieve with a pore size of 40 μm is used to remove large alloy powder particles larger than 40 μm, retaining alloy powder particles with a particle size less than or equal to 40 μm.
[0059] The metal injection molding preparation method for multi-element iron-silicon-aluminum soft magnetic parts provided by this invention involves mixing multi-element iron-silicon-aluminum alloy powder (by mass percentage) comprising 83-84% Fe powder, 7-7.5% Si powder, 5.5-6% Al powder, 1.0-1.2% Cr powder, 2.2-2.5% Ni powder, and 0.3-0.4% Cu powder as the metal powder raw material with polyoxymethylene, polyethylene, stearic acid, and antioxidants in a set ratio in a mixer for granulation. The granulated alloy feed particles are then subjected to injection molding, catalytic degreasing, thermal degreasing, sintering, and magnetic field annealing processes to prepare the multi-element iron-silicon-aluminum soft magnetic material. Because the multi-element iron-silicon-aluminum alloy powder incorporates three metallic elements—Ni, Cu, and Cr—and is combined with polyoxymethylene, polyethylene, stearic acid, antioxidants, and binders, the compatibility of the multi-element iron-silicon-aluminum alloy for metal injection molding is improved, preventing cracking of the preform after subsequent metal injection molding. Simultaneously, by introducing three metallic elements—Ni, Cu, and Cr—into the multi-element iron-silicon-aluminum alloy powder, and subsequently performing magnetic field annealing on the alloy sintered blank, the prepared multi-element iron-silicon-aluminum soft magnetic components possess advantages such as high frequency, low loss, strong corrosion resistance, and high toughness. This enables the mass production of multi-element iron-silicon-aluminum soft magnetic components using metal injection molding.
[0060] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and do not constitute a limitation on the scope of protection of the present invention. Equivalent adjustments or optimizations made by those skilled in the art based on the core concept of the present invention should still fall within the scope of protection of the present invention.
[0061] Example 1 S01, based on 100% of the total mass of the metal raw materials, provides the following metal raw materials: Fe 843%, Si 7%, Al 6%, Cr 1.2%, Ni 2.5%, Cu 0.3%.
[0062] S02, the various metal raw materials Fe, Si, Al, Cr, Ni and Cu are mixed and put into the vacuum induction melting furnace of the gas atomization equipment; the vacuum induction melting furnace is evacuated and heated to completely melt and refine the various metal raw materials to obtain a multi-element alloy liquid.
[0063] S03, the multi-element alloy liquid is transferred to the intermediate package of the gas atomization equipment. After flowing out through the leak in the intermediate package, nitrogen is used as the atomization medium to atomize the multi-element alloy liquid at an atomization pressure of 4MPa to obtain the initial multi-element iron-silicon-aluminum alloy powder.
[0064] S04. The initial multi-element iron-silicon-aluminum alloy powder is sieved using a vibrating screen with a pore size of 40μm to remove large alloy powder particles and obtain multi-element iron-silicon-aluminum alloy powder with a particle size of less than or equal to 40μm.
[0065] S11, formulated in the following mass percentage ratio (91%:6%:1.5%:1%:0.5%), provides the following components: multi-component iron-silicon-aluminum alloy powder, polyoxymethylene, polyethylene, stearic acid, and antioxidant. The multi-component iron-silicon-aluminum alloy powder is preheated in an internal mixer at a preheating temperature of 170℃ (T1) for 18 minutes.
[0066] Polyoxymethylene, polyethylene, stearic acid, and antioxidants were added to a mixer and mixed with preheated multi-element iron-silicon-aluminum alloy powder under the conditions of T2 of 160℃ and rotation speed V2 of 40r / min for 35min to obtain a uniform mixture.
[0067] S13, the mixture is fed into the granulator. The granulator uses a die with a diameter R1 of 3mm. The mixture is extruded and granulated under the condition of a rotation speed V3 of 180r / min to obtain alloy feed particles.
[0068] S21, the alloy feed particles are fed into the injection molding machine, and the temperature T3 of the heating zone of the injection molding machine is set to 180℃ to melt the alloy feed particles.
[0069] S22, control the screw speed V4 of the injection molding machine to 50 rpm and the back pressure P1 to 0.8 MPa, so that the molten alloy feedstock is conveyed forward in the injection molding machine, under the injection pressure of P2 of 110 MPa and V... 注射 The molten alloy feedstock is injected into the mold cavity at an injection speed of 40 mm / s.
[0070] S23, after injection is completed, the mold enters the holding pressure stage. The holding pressure time t3 is 8s. After cooling to room temperature, the mold cavity is opened and the part is ejected to obtain the alloy green blank.
[0071] S31, the alloy green blank is placed in a catalytic degreasing furnace heated to T4 (100°C), with a flow rate of V... 流1 The air inside the furnace was replaced under nitrogen protection at a rate of 0.4 L / min.
[0072] S32, oxalic acid is vaporized and then enters the furnace along with the carrier gas. The amount of oxalic acid introduced is V. 进酸 The alloy green blank was subjected to heat preservation and catalytic degreasing at a rate of 2 g / min for a catalytic degreasing time of t4 of 5 h, so that the polyoxymethylene in the alloy green blank underwent catalytic degradation and degreasing, resulting in a catalytically degreased alloy green blank.
[0073] S41, the catalytically degreased alloy green blank is placed in a vacuum furnace. After evacuation, the catalytically degreased alloy green blank in the vacuum furnace is heated in a stepped heating manner to gradually increase the furnace temperature to multiple incremental first preset temperature points, and held at each first preset temperature point for a first preset time. That is, the vacuum furnace temperature is raised from room temperature to T5 (350℃) and held for t5 (60 minutes) to remove some of the binder. Then, the temperature is raised from T5 to T6 and held for t6 (60 minutes), and T6 (600℃) to remove the residual binder, resulting in a hot-degreased alloy green blank.
[0074] S42, continue to heat up to V 温1 The hot degreased alloy green blank was heated from T6 to T7 at a heating rate of 3℃ / min and then held at 1250℃ for 3 hours to obtain a sintered blank.
[0075] S43, control the blank to V 温2 The alloy sintered billet was obtained by cooling at a rate of 10℃ / min.
[0076] S51, the alloy sintered blank is heated to T8 of 550℃ in a hydrogen atmosphere, the holding time is t8 of 2.5h, and a DC magnetic field of B of 0.2T is applied simultaneously, so that the direction of the DC magnetic field is consistent with the magnetization direction of the alloy sintered blank, thereby realizing the magnetic field heat treatment of the alloy sintered blank.
[0077] S52, in V 流2At a hydrogen flow rate of 0.8 L / min, with V 温3 The alloy sintered blank after magnetic field heat treatment was cooled at a cooling rate of 4℃ / min to room temperature to obtain a multi-element iron-silicon-aluminum soft magnetic part.
[0078] The multi-element iron-silicon-aluminum soft magnetic parts prepared by the metal injection molding method provided in Example 1 were subjected to relevant performance tests. The test results for each performance indicator are shown in Table 2. The specific testing standards / methods for each performance indicator are as follows: 1. Permeability (μ): According to the national standard GB / T 13091-2019 "Test Method for Magnetic Properties of Soft Magnetic Alloys", the test is conducted using an LCR digital bridge and a magnetic ring test fixture. The test frequency is 10kHz, and the test magnetic field is a low-field weak magnetic field (H < 1A / m). The soft magnetic component is processed into a standard toroidal sample (made of the same material and with the same process). After being placed in the permeability test fixture, the test frequency is set to 10kHz, the inductance L of the sample is measured, and the initial permeability μ is calculated according to the sample size and number of turns using a formula. The unit is dimensionless, and the test accuracy is ±1%.
[0079] 2. Coercivity (Hc): According to the national standard GB / T 3657-2021 "Measurement Method of DC Magnetic Properties of Soft Magnetic Alloys", the test is conducted using a soft magnetic DC BH magnetic property tester. The test mode is DC magnetization curve measurement, with a maximum applied magnetic field ≥1000A / m. The soft magnetic component is processed into a standard rod or sheet sample, placed in the test coil, a DC magnetic field is applied, and the hysteresis loop is measured. The coercivity Hc is directly read from the hysteresis loop, with the unit being A / m and the test accuracy being ±0.1A / m.
[0080] 3. Resistivity (ρ): According to the national standard GB / T 1410-2018 "Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials", a four-probe tester was used for testing. Before the test, the sample surface was polished flat and the oxide layer was removed. The cross-sectional area A and length L of the sample were measured. Then, the resistance R of the sample was measured by the four-probe method. The volume resistivity was calculated according to the formula ρ=R×A / L. The unit is μΩ·cm and the test accuracy is ±0.5μΩ·cm.
[0081] 4. High-frequency loss (10kHz~1MHz band): According to IEC 60404-3 "Magnetic materials - Part 3: Methods for measuring high-frequency magnetic properties of soft magnetic materials", an impedance analyzer was used in conjunction with a power loss test module for testing. The test frequencies were selected as 10kHz, 100kHz, and 1MHz, and the test conditions were sinusoidal excitation and constant Bm. A toroidal sample or a patch sample was used to measure the loss factor D, inductance L, and equivalent series resistance ESR at the corresponding frequencies, and then the unit volume loss P was calculated. sThe unit is mW / cm³, and the test accuracy is ±5mW / cm³.
[0082] 5. Salt spray corrosion resistance: According to the national standard GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test", the neutral salt spray test (NSS) was used for testing; the salt spray concentration was 5% NaCl solution, the test temperature was 35℃, the continuous spray mode was used, the rust condition of the sample surface was continuously observed, and the cumulative time without rust on the sample was recorded in h, with a test error of ±1h.
[0083] Table 1 shows the relevant process parameters for Examples 1-2 and Comparative Examples 1-2.
[0084] Example 2, Comparative Examples 1-2 The process flow and operation steps of the metal injection molding preparation method for multi-element iron-silicon-aluminum soft magnetic parts provided in Example 2, Comparative Examples 1 and 2 are the same as those in Example 1. The only difference is that the process parameter values corresponding to each step are adjusted according to the values shown in Table 1 below.
[0085] The performance indicators of the multi-element iron-silicon-aluminum soft magnetic components prepared in Example 2, Comparative Examples 1 and 2 were tested. The test results of each performance indicator are shown in Table 2.
[0086] Table 2 shows the performance test results of the multi-element iron-silicon-aluminum soft magnets prepared in Examples 1-2 and Comparative Examples 1-2.
[0087] Example 2, Comparative Example 1, Comparative Example 2 The process flow and operation steps of the metal injection molding preparation method for multi-element iron-silicon-aluminum soft magnetic parts provided in Example 2, Comparative Example 1, and Comparative Example 2 are the same as those in Example 1. The only difference is that the process parameter values corresponding to each process are adjusted according to the values shown in Table 1 below.
[0088] The performance indicators of the multi-element iron-silicon-aluminum soft magnetic components prepared in Example 2 and Comparative Examples 1-2 were tested. The test results of each performance indicator are shown in Table 2.
[0089] The test results of various performance indicators of the multi-element iron-silicon-aluminum soft magnetic components prepared in Examples 1-2 and Comparative Example 2 show that: the multi-element iron-silicon-aluminum soft magnetic component prepared in Comparative Example 1 has low magnetic properties due to the low Ni content in the metal raw materials used. The multi-element iron-silicon-aluminum soft magnetic component prepared in Comparative Example 2 has a significantly reduced density due to insufficient sintering temperature during sintering, which destroys the structural basis for the formation of soft magnetic properties. This results in insufficient diffusion and bonding of powder particles, a large number of micropores in the magnetic matrix, damage to the continuity of the magnetic domain structure, and impede domain movement, leading to a decrease in permeability and an increase in coercivity and high-frequency loss. In contrast, the multi-element iron-silicon-aluminum soft magnetic components prepared in Examples 1 and 2 have good performance indicators. This indicates that the metal injection molding method for preparing multi-element iron-silicon-aluminum soft magnetic components provided by this invention can achieve mass production of multi-element iron-silicon-aluminum soft magnetic components through the metal injection molding process. The multi-element iron-silicon-aluminum soft magnetic components prepared using the method provided in this invention possess advantages such as low high-frequency loss (loss ≤500mW / cm³ in the 10kHz~1MHz band), suitable permeability for high-frequency scenarios (μ≥1500), low coercivity (Hc≤8A / m), high resistivity (ρ≥100μΩ·cm), high corrosion resistance (salt spray resistance ≥72h), suitability for high-frequency scenarios from 10kHz to 1MHz, good magnetic property uniformity, and stable high-frequency loss. Furthermore, the green blanks of the multi-element iron-silicon-aluminum soft magnetic components show no cracking during preparation and no deformation after sintering, resulting in high dimensional accuracy (±0.3%).
[0090] In summary, the metal injection molding method for preparing multi-element iron-silicon-aluminum soft magnetic components provided by this invention uses a multi-element iron-silicon-aluminum alloy powder, comprising by mass percentage: 83-84% Fe powder, 7-7.5% Si powder, 5.5-6% Al powder, 1.0-1.2% Cr powder, 2.2-2.5% Ni powder, and 0.3-0.4% Cu powder, as the metal powder raw material. Because the multi-element iron-silicon-aluminum alloy powder introduces three metallic elements—Ni, Cu, and Cr—and is combined with binders including polyoxymethylene, polyethylene, stearic acid, and antioxidants, the compatibility of the multi-element iron-silicon-aluminum alloy for metal injection molding can be improved, avoiding cracking of the subsequent injection-molded or sintered blanks. Furthermore, the introduction of Ni, Cu, and Cr into the multi-element iron-silicon-aluminum alloy powder, combined with subsequent magnetic field annealing of the alloy sintered blank, results in multi-element iron-silicon-aluminum soft magnetic components with advantages such as high frequency and low loss, strong corrosion resistance, and high toughness. It can achieve mass production of multi-element iron-silicon-aluminum soft magnetic components through metal injection molding process.
[0091] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.
Claims
1. A method for preparing a multi-element iron-silicon-aluminum soft magnetic component by metal injection molding, characterized in that, Includes the following steps: S10, the following raw materials—multi-component iron-silicon-aluminum alloy powder, polyoxymethylene, polyethylene, stearic acid, and antioxidant—are added to a mixer in a set proportion and mixed. The mixture is then granulated using a granulator to obtain alloy feed pellets. The multi-component iron-silicon-aluminum alloy powder comprises, by mass percentage: 83-84% Fe powder, 7-7.5% Si powder, 5.5-6% Al powder, 1.0-1.2% Cr powder, 2.2-2.5% Ni powder, and 0.3-0.4% Cu powder. S20, alloy feed particles are fed into the injection molding machine, the injection temperature of the injection molding machine is controlled to melt the alloy feed particles, and the molten alloy feed particles are injected into the alloy green part. S30, the alloy green blank is subjected to catalytic degreasing to obtain a catalytically degreased alloy green blank; S40, the catalytically degreased alloy green blank is sequentially subjected to hot degreasing and sintering to obtain an alloy sintered green blank; S50 involves heating the alloy sintered blank in a reducing gas atmosphere and applying a DC magnetic field to achieve magnetic field heat treatment of the alloy sintered blank. After cooling, a multi-element iron-silicon-aluminum soft magnetic component is obtained.
2. The method for preparing a multi-element iron-silicon-aluminum soft magnetic component by metal injection molding according to claim 1, characterized in that, The procedure preceding step S10 also includes: S01, based on 100% total mass of metal raw materials, provides the following metal raw materials: Fe 83~84%, Si 7~7.5%, Al 5.5~6%, Cr 1.0~1.2%, Ni 2.2~2.5%, Cu 0.3~0.4%; S02, after mixing the various metal raw materials Fe, Si, Al, Cr, Ni and Cu, put them into the vacuum induction melting furnace of the gas atomization equipment; evacuate the vacuum induction melting furnace, heat it to completely melt and refine the various metal raw materials to obtain a multi-element alloy liquid; S03, the multi-element alloy liquid is transferred to the intermediate package of the gas atomization equipment. After flowing out through the leak in the intermediate package, nitrogen is used as the atomization medium to atomize the multi-element alloy liquid under atomization pressure to obtain the initial multi-element iron-silicon-aluminum alloy powder. S04, the initial multi-element iron-silicon-aluminum alloy powder is sieved to remove large alloy powder particles, and the multi-element iron-silicon-aluminum alloy powder is obtained.
3. The method for preparing a multi-element iron-silicon-aluminum soft magnetic component by metal injection molding according to claim 1, characterized in that, The morphology of the multi-element iron-silicon-aluminum alloy powder is spherical, with a sphericity greater than or equal to 0.85; The particle size of the multi-element iron-silicon-aluminum alloy powder is 0.1-40μm.
4. The method for preparing a multi-element iron-silicon-aluminum soft magnetic component by metal injection molding according to claim 1, characterized in that, The antioxidant is a hindered phenolic antioxidant.
5. The method for preparing a multi-element iron-silicon-aluminum soft magnetic component by metal injection molding according to claim 1, characterized in that, S10, the step of mixing the following raw materials—multi-element iron-silicon-aluminum alloy powder, polyoxymethylene, polyethylene, stearic acid, and antioxidant—in a mixer, followed by granulation in a granulator to obtain alloy feed pellets, specifically includes: S11, the multi-element iron-silicon-aluminum alloy powder is put into the internal mixer for preheating treatment; S12, polyoxymethylene, polyethylene, stearic acid and antioxidant are put into a mixer and heated and mixed with preheated multi-element iron-silicon-aluminum alloy powder to obtain a uniform mixture. S13, the mixture is fed into the granulator, which extrudes and granulates the mixture to obtain alloy feed pellets.
6. The method for preparing a multi-element iron-silicon-aluminum soft magnetic component by metal injection molding according to claim 1, characterized in that, S20, the step of feeding alloy feed particles into an injection molding machine, controlling the injection temperature of the injection molding machine to melt the alloy feed particles, and injection molding the molten alloy feed particles into an alloy green part specifically includes: S21, put the alloy feed particles into the injection molding machine, set the temperature of the heating zone of the injection molding machine, and melt the alloy feed particles; S22 controls the screw speed and back pressure of the injection molding machine, so that the molten alloy feedstock is conveyed forward in the injection molding machine and injected into the mold cavity; S23, after injection is completed, the process enters the holding pressure stage. After holding pressure is completed, the part is ejected from the mold cavity after cooling to obtain the alloy green blank.
7. The method for preparing a multi-element iron-silicon-aluminum soft magnetic component by metal injection molding according to claim 1, characterized in that, S30, the step of catalytically degreasing the alloy green blank to obtain a catalytically degreased alloy green blank, specifically includes: S31, place the alloy green blank in a heated catalytic degreasing furnace and replace the air in the furnace under nitrogen protection; S32, oxalic acid is vaporized and then introduced into the furnace along with the carrier gas to catalytically degrease the alloy green blanks, resulting in catalytically degreased alloy green blanks.
8. The method for preparing a multi-element iron-silicon-aluminum soft magnetic component by metal injection molding according to claim 1, characterized in that, S40, the step of sequentially hot degreasing and sintering the catalytically degreased alloy green blank to obtain a sintered alloy blank, specifically includes: S41, the catalytic degreasing alloy green blank is placed in a vacuum furnace. After evacuation, the catalytic degreasing alloy green blank in the vacuum furnace is heated by step heating, so that the furnace temperature is raised to multiple incremental preset temperature points in sequence, and the temperature is held at each preset temperature point for a set time to obtain the hot degreasing alloy green blank. S42, continue heating the hot degreased alloy green billet in the vacuum furnace to sinter and obtain a cooked billet; S43, the sintered billet is cooled to obtain the alloy sintered billet.
9. The method for preparing a multi-element iron-silicon-aluminum soft magnetic component by metal injection molding according to claim 1, characterized in that, S50, which involves heating the alloy sintered billet in a reducing gas atmosphere and applying a DC magnetic field to achieve magnetic field heat treatment of the alloy sintered billet, and obtaining a multi-element iron-silicon-aluminum soft magnetic component after cooling, specifically includes the following steps: S51, the alloy sintered billet is heated to 500~600℃ in a reducing gas atmosphere, held for 2~3h and a DC magnetic field of 0.1~0.3T is applied simultaneously, so that the direction of the DC magnetic field is consistent with the magnetization direction of the alloy sintered billet, thereby realizing the magnetic field heat treatment of the alloy sintered billet. S52, the alloy sintered billet after magnetic field heat treatment is cooled at a cooling rate of 3~5℃ / min, and after cooling to room temperature, a multi-element iron-silicon-aluminum soft magnetic part is obtained.
10. A multi-element iron-silicon-aluminum soft magnetic component, characterized in that, The composition by mass percentage includes: Fe 83-84%, Si 7-7.5%, Al 5.5-6%, Cr 1.0-1.2%, Ni 2.2-2.5%, Cu 0.3-0.4%; The multi-element iron-silicon-aluminum soft magnetic component is prepared by the metal injection molding method according to any one of claims 1 to 9.
